COMPARATIVE LEGAL REGULATION AND ENFORCEMENT OF SKIMMING CRIMES IN INDONESIA AND THE UNITED STATES OF AMERICA - Dian Eka Kusuma Wardani; Raodiah Raodiah; Indarahayu M. Umar Gazali; Dinara F. Abdunayimova (Universitas Syiah Kuala, 2025)
The rapid development of cybercrime as a form of digitally based criminal activity, including skimming, has increased significantly. Skimming is a criminal act that exploits technological advancements with the primary objective of data theft, most commonly occurring within the banking sector. This article examines and compares the legal regulation and enforcement of skimming crimes in Indonesia and the United States of America (USA), highlighting both similarities and differences between the two jurisdictions. This study employs normative legal research, emphasizing conceptual, comparative, and statutory approaches. The findings indicate that the regulation and enforcement of skimming crimes in Indonesia and the USA differ substantially due to variations in their legal systems and the readiness of law enforcement institutions. Indonesia continues to rely on general legal instruments, such as the Electronic Information and Transactions Law (UU ITE) and the Criminal Code, whereas the USA has implemented more specific and comprehensive regulations. These are supported by a flexible common law system, advanced law enforcement infrastructure, robust technological capabilities, and specialized institutions, resulting in more effective and efficient handling of skimming crimes. Consequently, future regulatory and law enforcement efforts in Indonesia should prioritize the development of a legal framework that is adaptive and responsive to the evolving nature of cybercrime, alongside strengthening human resources, enhancing law enforcement technology, and fostering cross-sectoral and international cooperation.